Rapid evolutionary loss of metal resistance revealed by hatching decades‐old eggs. (3rd February 2016) - Turko, Patrick; Sigg, Laura; Hollender, Juliane; Spaak, Piet
Abstract : We investigated the evolutionary response of an ecologically important freshwater crustacean, Daphnia, to a rapidly changing toxin environment. From the 1920s until the 1960s, the use of leaded gasoline caused the aquatic concentration of Pb to increase at least fivefold, presumably exerting rapid selective pressure on organisms for resistance. We predicted that Daphnia from this time of intense pollution would display greater resistance than those hatched from times of lower pollution. This question was addressed directly using the resurrection ecology approach, whereby dormant propagules from focal time periods were hatched and compared. We hatched several Daphnia genotypes from each of two Swiss lakes, during times of higher (1960s /1980s) and lower (2000s) lead stress, and compared their life histories under different laboratory levels of this stressor. Modern Daphnia had significantly reduced fitness, measured as the population growth rate (λ), when exposed to lead, whereas those genotypes hatched from times of high lead pollution did not display this reduction. These phenotypic differences contrast with only slight differences measured at neutral loci. We infer that Daphnia in these lakes were able to rapidly adapt to increasing lead concentrations, and just as rapidly lost this adaptation when the stressor was removed.